Association Between Hepatitis C Virus Infection and Clinical Atherosclerosis at The University Hospital of Cotonou, Comparative Cross- Sectional Study in 105 Patients - ADJAGBA, MAHOUNA PHILIPPE DOTOU; Kpossou, AR; SOKPON, MARTIN (My University, 2019)
Introduction: Many studies have shown that chronic hepatitis C virus (HCV) infection is an additional and independent risk factor for coronary heart disease, carotid atherosclerosis and cerebrovascular accidents (stroke). The purpose of this work was to study the association between HCV infection and clinical atherosclerosis in a hospital in Cotonou. Patients and Methods: This was a comparative cross-sectional study that took place from 02 to 30 November 2018 at the Department of Cardiology at the University Hospital of Cotonou. The cases followed were patients followed for clinical atherosclerosis and were compared to controls with no clinical history of atherosclerosis and followed for diagnosed hypertension (hypertension) less than 5 years old. Sociodemographic data and the prevalence of HCV infection were compared in the two groups. The diagnosis of hepatitis C virus (HCV) infection was performed by a Hepatitis C Virus Test Strip® rapid diagnostic orientation test, HCV confirmation serology by ELISA (Enzymelinked immunosorbent assay) and the "Polymerase Chain Reaction" (PCR) for the determination of the HCV viral load. Data analysis was performed using EpiData version 3.1 and Epi Info software. A value of p<0.05 was considered statistically significant. Results: Among the 105 subjects included, there were 53 cases (50.3%) and 52 controls (49.5%). The mean age of the subjects was 59.7 years ± 11.0 with no significant difference between cases and controls (p=0.56). Cases and controls were comparable across all conventional atheromatous risk factors outside of hypertension, which had a higher prevalence among controls (p=0.002). Acute coronary syndrome was the most common clinical form of atherosclerosis in 94.3% of cases. Of the 105 subjects in the study, the HCV rapid screening test was positive in 4 (3.8%), including 2 cases (3.8%) and 2 controls (3.8%). There was no significant association between HCV infection and the presence of clinical atherosclerosis (p=0.68). One of the two cases had an undetectable charge. Conclusion: Chronic HCV infection would not be associated with clinical atherosclerosis in our study. A larger study, including a larger number of cases and controls, is needed to clarify these data.
Keywords: Hepatitis C; Clinical atherosclerosis; Association.